Strategic entente or non-alignment : a refinement of India's foreign policy (1946-1955) - Amarjit Singh Grewal (2009)
This study on India's policy of non-alignment was a learning experience in many ways. The interviews with Indian scholars and former policymakers is one illustration of why this is true. They showed that unofficial information does have a quality that at times supersedes official sources in research.